Influence of Organisational Climate and Personal Factors on the Teaching Self-Efficacy of Nursing Educators Teaching in Higher Education Institutions in Pakistan - Kousar, Sameena (2023)
Nursing education in Pakistan has undergone significant changes since last years. The most important is transition of nursing diploma into degree programme. Due to this transition, higher education institutions in Pakistan are indeed relying on experiencedclinical nursing educators to assume the role of an academic educator. This can cause role strain and consequently, nursing educators may experience inability to efficiently teach nursing students in the classroom. Further, organisational climate of higher educational institutions may also call in question the quality of education nursing educators deliver. Thus, this co-relational study was conducted to determine the relationship of organisational climate and the influence of personal factors on their classroom teaching-efficacy. This study also determined the nursing educators’ personal and organisational level best predictors of teaching efficacy. Purposive sampling technique was employed. Study was conducted in twelve medical universities of Pakistan considering the nursing educators as study population. Two hundred and twenty nursing educators qualifying inclusion criteria were considered as sample. Teachers’ Sense of Efficacy Scale and Organisational Climate Description Questionnaire for Higher Education were employed to assess nursing educators’ perception of teaching efficacy and organisational climate. Mean & SD were calculated for nursing educators’ demographics and self-efficacy dimensions. Analysis of Variance was conducted to assess differences among teaching self-efficacy dimensions with regard to personal factors of age and teaching experience. Significance of differences between pairs of age and teaching experience groups means was calculated through Post hoc-tukey test. Independent t test was run to determine the difference in teaching efficacy dimensions with regard to qualifications level. Correlation among organisational climate and teaching efficacy was estimated by correlation coefficient. A multiple regression was conducted to determine best personal and organisation-level predictor. This study has provided evidence that nursing educators senior in age with longer years of teaching experience perceived themselves more competent at facilitating classroom teaching than novice colleagues. Moreover, the study also found that organisational climate impacts nursing educators' teaching efficacy. From personal level predictor, teaching experience and from organisational level predictor consideration; head of department supportive behavior has been found strong predictor of nursing educators’ teaching efficacy. Overall, the findings of this study provide valuable insights into the factors contributing to nursing educators' teaching efficacy. These findings can be used to inform the development and support of nursing educators to ensure that nursing students receive the highest quality education.